Pengggunaan Drone (Pesawat Tanpa Awak) Dalam Komplik Bersenjata Menurut Presfektif Hukum Udara Internasional Serta Pertanggungjawabannya - Gun Ramajayadi; Dwi Putri Lestarika; Wevy Efticha Sary (GLOBAL SCIENTS PUBLISHER, 2025)
State sovereignty over airspace according to international law is complete and comprehensive. However, in practice, the use of unmanned aircraft (drones) has not been specifically regulated through international regulations or conventions. The slow development of drone regulations is due to the absence of laws and standards from the International Civil Aviation Organization (ICAO). This study aims to examine the legality of drones crossing state borders and Yemen's responsibility for the actions of the Houthi rebels. This study uses a normative legal method with a descriptive approach, using secondary data analyzed qualitatively, and drawing conclusions deductively. The results of the study show that although drones are equated with aircraft in their regulations, the term drone has not been explicitly regulated in national or international air law.